Genomic structural equation study reveals links between anorexia nervosa and delay discounting and lack of perseverance but not other facets of impulsivity - Sevim B. Bianchi; Sevim B. Bianchi; Laura Vilar-Ribó; Abraham A. Palmer; Abraham A. Palmer; Daniel E. Gustavson; Sandra Sanchez-Roige; Sandra Sanchez-Roige; Sandra Sanchez-Roige (Frontiers in Psychiatry, 2025)
Anorexia nervosa (AN) is a heritable condition, characterized by a fear of weight gain and a distorted body image, for which treatments are only limited. AN is characterized by excessive control over feeding behaviors, which has been hypothesized to indicate that low impulsivity, including low emotional impulsivity (urgency), may place certain individuals at risk for AN; however, this has not been fully genetically evaluated. We used genomic structural equation modeling and genome-wide association studies (GWASs) based on individuals of European ancestry (n = 72,517–903,147) to examine the latent genetic architecture between AN and several measures of impulsivity. Because AN is positively genetically associated with substance use disorders (SUDs), which are also strongly associated with impulsivity, we conditioned our analyses using GWAS data from four SUDs (alcohol, tobacco, cannabis, and opioid use disorders). AN was not significantly genetically correlated with impulsivity latent factors as indices of Barratt Impulsiveness Scale (BIS) or Urgency, Premeditation, Perseverance, Sensation Seeking, and Positive Urgency (UPPS) subscales (common impulsivity, rg = −0.07; urgency-specific impulsivity, rg = 0.14; and sensation seeking, rg = −0.07) but was significantly negatively genetically correlated with delay discounting (rg = −0.19) and lack of perseverance (rg = −0.15), even after controlling for SUDs (rg = −0.32 or rg = −0.25, respectively). This work suggests that delay discounting and lack of perseverance capture genetically informative dimensions of AN; clarifying shared etiologies could inform AN diagnosis and treatment mechanisms.